PPIUCD: awareness and reasons for non-acceptance - Alukal, Anila Tresa; Raveendran, Resmy C.; George, Lissiamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The recommended interval between pregnancies is at least 24 months in order to reduce the risk of adverse maternal, perinatal and infant outcomes. Ministry of Health & Family Welfare, Government of India has taken initiative for provision of IUCD in immediate postpartum period. Several training programs and awareness camps are conducted by NHM for health service providers and also for the public. The aim of the study was to determine proportion of women accepting post placental intrauterine Contraceptive Device insertion, and to describe the factors associated with acceptability and non-acceptance. Methods: The study was conducted at the Government Medical College Thrissur, Kerala, India and study period was 1 year (2014-2015). The study population included women who planned to deliver at Government Medical College, Thrissur during the study period including vaginal and caesarean section. Results: The awareness regarding PPIUCD was only 11.1% whereas for interval IUCD it was 94.9%. The acceptance rate of PPIUCD was very low (10.5%). The most common reason to accept was its long action (68.5%) The most common reason for rejection was that they wanted permanent sterilisation. The other reasons for non-acceptance include unwillingness of husband, fear of complications etc. Conclusions: The acceptance rate was very low even though majority of the study population were well educated. The most common reason for acceptance was long action followed by reversibility.The reasons for refusal like unwillingness of husband, fear of complications etc. can be overcome by proper counselling and public awareness programs.